STRATEGI PENGUATAN NILAI-NILAI KEAGAMAAN PADA SISWA SMP BUSTANUL MAKMUR GENTENG BANYUWANGI - Duvaliani Nadya Karenina; Ahmad Subekti; Imam Syafi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This study aims to find out how the strategy of strengthening religious values in students of Bustanul Makmur Genteng Banyuwangi Junior High School. Strengthening religious values done by habituation is a motivation for students to be able to learn, and also practice in the life of society. Not only habituation, but also hammering the funding that teachers give to their students. By giving examples of doing small things but having meaning and benefits that are quite influential, is one of the strategies in providing strengthening religious values to students. There are several supporting factors and inhibitions in providing strengthening of religious values to students that must be considered in order to achieve the goal. The impact of strengthening religious values itself is positive because it can build motivation on students in learning religious values that can be beneficial for religious life and society later.